Colonial Entanglements and Ecological Power: Spice Commodification in Dune Movie (2021) - Prihatika, Yusrina Dinar (Lingua Susastra, 2024)
This study examines the themes of colonial entanglement and ecological power in the film Dune (2021), focusing on the commodification of the spice "melange" on Arrakis. Using postcolonial ecocriticism and cultural studies frameworks, it explores how the film portrays environmental exploitation and the marginalization of the indigenous Fremen. The analysis reveals how colonial powers, like House Harkonnen and House Atreides, dehumanize and oppress the Fremen, ignoring their ecological knowledge and cultural significance. By drawing parallels to real-world colonial histories, the study highlights the film's critique of environmental degradation and cultural marginalization. It underscores the importance of recognizing indigenous knowledge and rights for sustainable and equitable resource management. This interdisciplinary approach provides insights into the ongoing relevance of colonial power dynamics and resource commodification in contemporary society.